2022
DOI: 10.3390/md20010059
|View full text |Cite
|
Sign up to set email alerts
|

Sonneradon A Extends Lifespan of Caenorhabditis elegans by Modulating Mitochondrial and IIS Signaling Pathways

Abstract: Aging is related to the lowered overall functioning and increased risk for various age-related diseases in humans. Sonneradon A (SDA), a new compound first extracted from the edible fruits of mangrove Sonneratia apetala, showed remarkable antiaging activity. However, the role of SDA in antiaging remains unclear. In this article, we studied the function of SDA in antiaging by using the animal model Caenorhabditis elegans. Results showed that SDA inhibited production of reactive oxygen species (ROS) by 53%, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 49 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…Sonneradon A ( 282 ), isolated from the edible fruits of mangrove Sonneratia apetala , showed remarkable antiaging activity, which inhibited production of reactive oxygen species (ROS) by 53%, and reduced the accumulation of aging markers such as lipids and lipofuscins [ 77 ]. Three new chlorinated orsellinic aldehyde derivatives, orsaldechlorins A–C ( 283 – 285 ) and a naturally new brominated orsellinic acid ( 286 ), were identified from the Beibu Gulf coral-derived fungus Acremonium sclerotigenum GXIMD 02501.…”
Section: New Mnps From the Beibu Gulfmentioning
confidence: 99%
“…Sonneradon A ( 282 ), isolated from the edible fruits of mangrove Sonneratia apetala , showed remarkable antiaging activity, which inhibited production of reactive oxygen species (ROS) by 53%, and reduced the accumulation of aging markers such as lipids and lipofuscins [ 77 ]. Three new chlorinated orsellinic aldehyde derivatives, orsaldechlorins A–C ( 283 – 285 ) and a naturally new brominated orsellinic acid ( 286 ), were identified from the Beibu Gulf coral-derived fungus Acremonium sclerotigenum GXIMD 02501.…”
Section: New Mnps From the Beibu Gulfmentioning
confidence: 99%
“…To date, the heat shock genes (hsp genes) and the Hsp proteins they encode have been best studied and described in the free-living bacterivorous nematode Caenorhabditis elegans (Maupas, 1900). Studies have shown that the expression of hsp genes influences the lifespan of C. elegans [6][7][8]. It has also been shown that hsp genes in C. elegans are induced in response to various stressors, such as oxidative stress [9][10][11], electromagnetic field [12][13][14], immunological stress [15][16][17], or toxic chemical compounds [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The fruit contains a high content of nutrients, polyphenols, flavonoids, vitamin C, and antioxidants. The fruit exhibits the following health-promoting activities: anti-diarrheal, analgesic, hepatoprotective, anti-aging, and inhibition of elastase-induced lung injury ( Hossain et al, 2016a , 2017 ; Liu et al, 2019 ; Yi et al, 2020 ; Jiang et al, 2022 ; Sengupta et al, 2022 ). Moreover, S. apetala fruit is second to Emblica officinalis in its content of polyphenols [48 mg gallic acid equivalent (GAE)/g powder] among the edible fruits in Bangladesh ( Hosen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%